2001
DOI: 10.1175/1520-0485(2001)031<2917:tdotea>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics of the East Australian Current System: The Tasman Front, the East Auckland Current, and the East Cape Current

Abstract: The dynamics of the flow field surrounding New Zealand are investigated using a series of global ocean models. The physical mechanisms governing the direction, magnitude, and location of the East Australian Current (EAC), the Tasman Front, the East Auckland Current (EAUC), and the East Cape Current (ECC) are studied using numerical simulations whose complexity is systematically increased. As new dynamics are added to each successive simulation, their direct and indirect effects on the flow field are examined. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
121
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 134 publications
(128 citation statements)
references
References 53 publications
5
121
2
Order By: Relevance
“…1) manifests as an eastward 'zonal jet' between 152 ‡ and 173 ‡E, connecting the East Australian Current (EAC) with the East Cape Current (ECC) northeast of New Zealand (Warren, 1970). Numerous eddies are associated with this frontal zone (Tilburg et al, 2001) and surface waters are characterized by an abrupt change in temperature and salinity (Heath, 1985). Scott (1981) observed seasonally elevated phytoplankton £uorescence within some eddies along the TF, and Comiso et al (1993) found a positive correlation between seasonally elevated chlorophyll concentrations and the strength of Ekman upwelling in the Tasman Sea.…”
Section: Oceanographic Settingmentioning
confidence: 95%
“…1) manifests as an eastward 'zonal jet' between 152 ‡ and 173 ‡E, connecting the East Australian Current (EAC) with the East Cape Current (ECC) northeast of New Zealand (Warren, 1970). Numerous eddies are associated with this frontal zone (Tilburg et al, 2001) and surface waters are characterized by an abrupt change in temperature and salinity (Heath, 1985). Scott (1981) observed seasonally elevated phytoplankton £uorescence within some eddies along the TF, and Comiso et al (1993) found a positive correlation between seasonally elevated chlorophyll concentrations and the strength of Ekman upwelling in the Tasman Sea.…”
Section: Oceanographic Settingmentioning
confidence: 95%
“…Further, water temperatures within the high latitude foraging areas of the EAC are warmer than temperate waters frequented by leatherbacks in the northern hemisphere, thus potentially providing an energetic advantage. Tasman Front (TAS).-The TAS is a semipermanent frontal feature created by the East Australia Current as it moves eastward and offshore, and is characterized by marked meanders and eddies and a zone of enhanced CHL (Andrews et al 1980, Tilburg et al 2001, Belkin and Cornillon 2007, Baird et al 2008. Two leatherbacks from SI nesting beaches arrived in the TAS region during April-June and engaged in ARS behavior in an area of low currentvelocity and potential zooplankton retention just south of the TAS prior to passing New Zealand's North Cape (Fig.…”
Section: High-use Foraging Destinationsmentioning
confidence: 99%
“…The EAC flows dominantly southwards from the Coral Sea to the north of Sydney. Here, a large proportion of it deflects eastwards or recirculates (Ridgway and Godfrey 1997), whereas about a third continues southwards to the Tasman Sea, as a weaker, less reliable current (Tilburg et al 2001). This most southerly flow is twice as strong in the austral summer than in winter, reflecting seasonal changes in the intensity of anti-cyclonic eddies formed along its path (Ridgway and Godfrey 1997).…”
Section: Introductionmentioning
confidence: 98%